A PURPOSE CONCEPTUAL FRAMEWORK TO EXAMINE THE CORRELATON OF LOGISTICS SERVICE QUALITY, LOGISTICS PERFORMANCE & COMPETITIVE ADVANTAGE OF LOGISTICS SERVICE PROVIDERS IN THAILAND (Journal of Technology and Operations Management, 2024)
The logistics service offers a crucial role in the process of developing into the worldwide market. Several nations must enhance their logistics service operations to achieve strong performance and attain a competitive edge in the market. Logistics service quality is a crucial element in Thailand's logistics operations. It is a major feature in developing a new conceptual model for logistics service performance, which is essential for achieving competitiveness in the logistics sector. The aim of this study is to investigate the relationship between the framework of logistics service quality, logistics performance and competitive advantage of logistics service provider (LSPs) firms in Thailand. This study utilizes primary data and applies a quantitative methodology, involving the collecting and analysis of research data using a strategy that emphasizes quantification. The sample will be LSPs companies in Thailand. The future data in this study will be analyzed using the statistical software packages SPSS and Smart PLS. Partial least squares structural equation modelling (PLS-SEM) is a statistical method employed for data analysis, with the primary goal of enhancing the research model. Thus, the study presents a conceptual framework that suggests that enhancing service quality can improve the logistics performance and competitive advantage of the logistics service provider business in Thailand.